Peningkatan Pendapatan Petani melalui Implementasi Teknologi Solar Water Pump pada Perkebunan - Agus Nisfur Romdioni; Cipto Cipto; Daniel Parenden (Lembaga Pengembangan Kinerja Dosen, 2025)
Water is the main need for every living creature, including humans. However, sometimes the springs are located under residential areas. To lift water to residential areas, large amounts of electrical energy are needed to drive water pumps. Apart from the very large electrical energy sources required, the price of water pumps is very expensive, it is necessary to develop alternative energy sources. An alternative energy source that has enormous potential in Indonesia is solar energy. Every year the sun releases 745 thousand trillion kWh of solar energy reaching the earth. In connection with the above, dedication was carried out regarding the design of the solar water pump. In the design of the solar water pump, a DC water pump is used with a solar power source using 3 solar panel modules. Through the Mitra Village Service SKIM, LPPM UNMUS 2024 Program, this service will examine the performance of the solar water pump, namely the maximum power produced by the solar panels, the water flow that can be lifted by the pump and the duration of operation in a day. The results of service activities in the form of technology that has been installed in partner plantations in Waninggap Nanggo Village, this technology is able to save on plantation operations, especially water pump electricity costs, by using solar power sources. Based on the analysis, electricity costs have been saved by 30%, thereby increasing partner income.